Flour babies (London Puffin Books, 1994)
When his class of underachievers is assigned to spend three torturous weeks taking care of their own "babies" in the form of bags of flour, Simon makes amazing discoveries about himself while coming to terms with his long-absent father.
Keywords: Infants -- Juvenile fiction; Parent and child -- Juvenile fiction; Parenting -- Juvenile fiction; Schools -- Juvenile fiction; English fiction